ANALISIS PENGARUH KUALITAS LAYANAN DAN PERSEPSI ATAS HARGA TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN (Studi Kasus Pada Konsumen Bus Pariwisata PO Jaya Indah Semarang) - Pramana, Riyan Indra; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2016)
The background of this research is the salesÂ decline PO Jaya Indah Semarang in the period 2012-2014. , The decline in sales can be formulated that how consumers feel satisfied and loyal after using PO Jaya Indah Semarang amid increasingly fierce competition phenomenon. This study aimed to examine the effect of Quality of Service , Perception of Price on Consumer Loyalty through Customer Satisfaction on tourist buses PO Jaya Indah Semarang. Samples were consumers buses PO Jaya Indah Semarang, amounting to 100 people. Data analysis method used is quantitative analysis using multiple linear regression analysis.Quantitive methods include the validity and reliability, the classic assumption test, testing hypothesis through F test, t test and the coefficient of determination (R2). And in this study using Sobel test to detect Customer Satisfaction as intervening variable. The results showed that the Quality of Service and Perception of Price showed a positive influence on Customer Satisfaction, Customer Satisfaction subsequently accepted as an intervening variable in mediating the Quality of Service and Perception of Price to Consumer Loyalty.